Negating As a Textual - Conceptual Tool in selected poems of Maya Angelou: A Critical Stylistic Analysis - Haider Saleh Abdulhusain (مجلة الباحث, 2025)
This study uses a critical stylistic structure to examine how linguistic selections create conceptual meaning in Maya Angelou's poetry. The paper analyses chosen poems to show how Angelou employs negation—both as a grammatical structure and as a rhetorical device—to dispute main narratives, claim identity, and show resistance. The study examines how negation interacts with other stylistic structures to provide new perspectives and empower marginalized lines using Jeffries' Critical Stylistics model. The replies show that Angelou's denial eliminates cruel beliefs and affirms self-worth and agency. The research concludes that Angelou uses negation to reclaim narrative interplanetary and redefine cultural dissertation.